2021
DOI: 10.3390/ijms22168949
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New AIEE-Active Chalcones for Imaging of Mitochondria in Living Cells and Zebrafish In Vivo

Abstract: Fluorophores with aggregation-induced emission enhancement (AIEE) properties have attracted increasing interest in recent years. On the basis of our previous research, we successfully designed and synthesized eleven chalcones. Through an optical performance experiment, we confirmed that compounds 1–6 had obvious AIEE properties. As these AIEE molecules had excellent fluorescence properties and a large Stokes shift, we studied their application in living cell imaging, and the results showed that these compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…This indicates that with the gradual Increase in the water content in the mixed solution, new aggregates were formed in the solution, which led to the gradual enhancement of the fluorescence emission of the compounds. This is consistent with our previous study [ 33 ].…”
Section: Resultssupporting
confidence: 95%
See 2 more Smart Citations
“…This indicates that with the gradual Increase in the water content in the mixed solution, new aggregates were formed in the solution, which led to the gradual enhancement of the fluorescence emission of the compounds. This is consistent with our previous study [ 33 ].…”
Section: Resultssupporting
confidence: 95%
“…In our previous study, we found that RIR is supposed to be the main reason for the AIEE properties of the flavonoids, flavones, and chalcones we investigated [ 32 , 33 ]. The same experimental approaches were used to explore the cause of the AIEE phenomenon of compounds 1 – 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At f w = 95%, the emission bands were distributed equally at both wavelengths. We believe as the hydrophobic anthracene rings repel water, they minimize their contact with water and thus rupture the aggregates beyond a water percentage of 70% [ 62 , 63 ]. Figure 1 b displays changes at various percentages of water varying from 10% to 95% in a MeOH-H 2 O system under UV light.…”
Section: Resultsmentioning
confidence: 99%
“…Organic luminophores with high quantum efficiencies have attracted attention due to their widespread applications in organic optoelectronics [1][2][3], laser displays [4,5], lightemitting diodes (OLEDs) [6], fluorescent sensors and biological imaging [7][8][9][10]. However, many traditional fluorophores usually show strong fluorescence only in dilute solutions.…”
Section: Introductionmentioning
confidence: 99%